Dukungan Pasangan pada Pasien Kanker Payudara yang Menjalani Kemoterapi di RSI Sultan Agung Semarang - Nurhidayati, Tri; Rahayu, Desi Ariyana (Jurnal Keperawatan Soedirman, 2017)
Breast cancer is a disease than can afflect anyone, especially in women, and any type of treatment of breast disease can cause physiological, phychological and social problems in women. Body image can change due to psychological response for breast cancer patients. This study aims to determine the support of couples in breast cancer who get chemotherapy. The design of this research was qualitative using descriptive phneomenology. The finding of this research was couples support intrumental,award, emotional, and information. Suggestion their couples provided information actively and asked nurse or doctor during chemoterapy